Clinical interpretation of cell-based non-invasive prenatal testing for monogenic disorders including repeat expansion disorders: potentials and pitfalls - Jeppesen, Line Dahl; Hatt, Lotte; Singh, Ripudaman; Schelde, Palle; Ravn, Katarina; Toft, Christian Liebst; Laursen, Maria Bach; Hedegaard, Jakob; Christensen, Inga Baasch; Nicolaisen, Bolette Hestbek; Andreasen, Lotte; Pedersen, Lars Henning; et al. (Frontiers in Genetics, 2023)
Introduction: Circulating fetal cells isolated from maternal blood can be used for prenatal testing, representing a safe alternative to invasive testing. The present study investigated the potential of cellbased noninvasive prenatal testing (NIPT) for diagnosing monogenic disorders dependent on the mode of inheritance.Methods: Maternal blood samples were collected from women opting for prenatal diagnostics for specific monogenic disorders (N = 7). Fetal trophoblasts were enriched and stained using magnetic activated cell sorting and isolated by fluorescens activated single-cell sorting. Individual cells were subject to whole genome amplification, and cells of fetal origin were identified by DNA-profiling using short tandem repeat markers. The amplified fetal DNA was input for genetic testing for autosomal dominant-, autosomal recessive-, X-linked and repeat expansion disorders by direct variant analysis and haplotyping. The cell-based NIPT results were compared with those of invasive testing.In two cases at risk of skeletal dysplasia, caused by variants in the FGFR3 gene (autosomal dominant disorders), cell-based NIPT correctly stated an affected fetus, but allelic dropout of the normal alleles were observed in both cases. Cell-based NIPT gave an accurate result in two cases at risk of autosomal recessive disorders, where the parents carried either different diastrophic dysplasia causing variants in the SLC26A2 gene or the same cystic fibrosis disease-causing variant in the CFTR gene. Cell-based NIPT accurately identified an affected male fetus in a pregnancy at risk of Duchenne muscular dystrophy (DMD gene, X-linked recessive disorders). In two cases at risk of the myotonic dystrophy type 1 (DMPK gene, repeat expansion disorder), cell-based NIPT correctly detected an affected and an unaffected fetus, respectively. Discussion: Circulating fetal cells can be used to detect both maternally-and paternally inherited monogenic disorders irrespective of the type of variant, however, the risk of allelic dropout must be considered. We conclude that the clinical interpretation of the cell-based NIPT result thus varies depending on the disorders' mode of inheritance.